Determination of Nicotine Extracted from Eggplant and Green Pepper by HPLC (Baghdad Science Journal, 2019)
Nicotine was separated from eggplant and green pepper seeds (Solanaceous) by High Performance Liquid Chromatography (HPLC).The concentration of nicotine in the eggplant extract (0.871-0.877 μg/ml) was determined by injecting standard material with 0.5 and 1.5 μg/ml, while the concentrations of nicotine in green pepper extract (0.613-0.618 μg/ml) was determined when the standard material was injected with 0.5 and 1.5 μg/ml. The qualitative chemical data was calculated from derivations of the standard material. Nicotine concentration was measured qualitatively in both extracts through the calibration curve and method of the standard addition. This technique has high accuracy and compatibility, bringing the proportion of relative recovery percentage of nicotine extracted from eggplant seeds to 95.880-103.104% and relative error of -4.119-3.104%. Relative recovery percentage of nicotine extracted from green pepper seeds was 97.284 -103.518 % and relative error was -2.716-3.518%.